2020
DOI: 10.1038/s41586-020-2607-z
|View full text |Cite|
|
Sign up to set email alerts
|

Single-shot Ad26 vaccine protects against SARS-CoV-2 in rhesus macaques

Abstract: A safe and effective vaccine for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may be required to end the coronavirus disease 2019 (COVID-19) pandemic 1 – 8 . For global deployment and pandemic control, a vaccine that requires only a single immunization would be optimal. Here we show the immunogenicity and protective efficacy of a single dose of adenovirus serotype 26 (Ad26) vector-based vaccines expressing the SARS-CoV-2 spike (S) protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

72
972
5
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 815 publications
(1,071 citation statements)
references
References 34 publications
(54 reference statements)
72
972
5
7
Order By: Relevance
“…We demonstrate that strongly increased antibody responses are generated already by the hexamerization scaffold, however most potent responses were obtained by scaffolds that form large oligomers. Antibody titers in this study were comparable to several other vaccines that advced to clinical trials 4,5,7,9 .The size and the degree of multimerization was not the only important factor for the observed level of neutralization as the RBD-AaLs that presents 60 copies of the antigen was less efficient in comparison to the 24 copies of the RBD presenting RBD-ferritin and 6 copies in the RBD-foldon-RBD. One reasons for the difference could be that the lumazine synthase presents the antigen in a different spatial arrangement in comparison to foldon and ferritin, while in RBD-bann assembly the presented oligomeric unit of the RBD may be governed by the intrinsic oligomerization propensity of the RBD.…”
Section: Immune Response Against the Scaffold In A Genetic Fusion Witsupporting
confidence: 72%
See 2 more Smart Citations
“…We demonstrate that strongly increased antibody responses are generated already by the hexamerization scaffold, however most potent responses were obtained by scaffolds that form large oligomers. Antibody titers in this study were comparable to several other vaccines that advced to clinical trials 4,5,7,9 .The size and the degree of multimerization was not the only important factor for the observed level of neutralization as the RBD-AaLs that presents 60 copies of the antigen was less efficient in comparison to the 24 copies of the RBD presenting RBD-ferritin and 6 copies in the RBD-foldon-RBD. One reasons for the difference could be that the lumazine synthase presents the antigen in a different spatial arrangement in comparison to foldon and ferritin, while in RBD-bann assembly the presented oligomeric unit of the RBD may be governed by the intrinsic oligomerization propensity of the RBD.…”
Section: Immune Response Against the Scaffold In A Genetic Fusion Witsupporting
confidence: 72%
“…An effective vaccine should trigger formation of a protective humoral and cell mediated immune response against the viral components that will either inhibit viral entry and replication or kill virus-infected cells. Different vaccination platforms for the presentation of viral components have been used, including inactivated or attenuated viral particles, purified proteins, mRNA, plasmid DNA, nonreplicating viruses; each of them with particular features [4][5][6][7][8][9] . The advantages of DNA plasmid delivery including the speed of adaptation to new targets, cost effective production, stability at ambient temperature without the need for a cold chain make it a potentially attractive vaccination platform, although no DNA plasmid vaccine has been approved for humans so far 10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A safe and effective vaccine is the need of the hour to overcome the COVID-19 pandemic. In the global race for the development of vaccines, few research groups have reported the preclinical studies of viral vector vaccines (ChAdOx1 nCoV-19 and Ad-26.COV.2.S) 4,5 , mRNA vaccine (mRNA-1273) , DNA vaccine (INO-4800) 7 and inactivated vaccines (PiCoVacc and BBIBP-CorV) 8,9 . Phase I/II clinical trial are either completed or on-going for these vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The scienti c community, including critical industry and academic partnerships, have embarked on an unprecedented race to develop and produce effective COVID-19 vaccine(s) for global use 1 . Several recent reports validate the SARS-CoV-2 Spike (S) protein as a promising target for COVID-19 vaccine development [2][3][4][5] . However, these approaches utilise platforms based on nucleic acids, viral vectors or insect cell production systems which could face challenges during large-scale manufacture and distribution.…”
Section: Introductionmentioning
confidence: 94%